DARI MATA LALU TURUN KE HATI : SHOW WINDOW, FEEL GOOD DAN PURCHASE INTENT ZARA PADA KONSUMEN WANITA DI SURABAYA - Jimmi Sutono; Dudi Anandya; Christina R. Honantha (CALYPTRA, 2018)
This study aims to prove the effect of show window towards purchase intent mediated by feel good inZARA,Surabaya. This type of research is causal research with quantitative approach. This study using purposive sampling approach, which is a sampling technique based on the consideration or personal judgment of researchers associated with the characteristics of the population according to the research sample. Thecharacteristics is respondents who visited ZARA and make some buy after seek a show window ZARAin the last one year. Respondents in this study amounted to 168 people. The analysis in this study using a model of SEM (Structural Equation Modeling) and processed using SPSS software version 22.0 for Windows and AMOS version 22.0 for Windows for testing Measurement and Structural Model. The result of this study indicate that allhypothesis supported such show window towards purchase intent and show wndow towards purchase intent mediated by feel good.